PRESTASI KERJA DITINJAU DARI MOTIVASI BERPRESTASI PADA KARYAWAN PT.CIPTA MANDIRI PERKASA - Suhendro Hadi Saputro; Flora Grace Putrianti (Universitas Sarjanawiyata Tamansiswa, 2013)
AbstractÂ The purpose of this study is to determine the relationship between job performance and achievement motivation in employees. Subjects in this study were employees PT.Cipta Mandiri Perkasa Yogyakarta. Sampling technique was purposive sampling. The method of analysis used in this study is Product Moment by Karl Pearson.Results of data analysis variable performance with achievement motivation variable indicates the value of r 0.750 p = 0.000 (p < 0,05). Based on the results of the correlation can be stated that there is a significant positive relationship between achievement motivation with the work performance of employees.Correlation test results showed that achievement motivation variables with job performance determinant coefficient has a value of 0.563. Means of achievement motivation variables contribute effectively to the work performance of 56.30 % , while the remaining 43.70 % is influenced by other factors such as job satisfaction, stress level, physical working conditions, compensation systems and job design.Â Keywords : Achievement motivation, work performance of employees.Â